A study on a stone lantern from Dongzhang village in medieval China - Chen, Huaiyu (Studies in Chinese Religions, 2019)
The lamp platform was one of the most interesting architectural designs in medieval Chinese Buddhism. Its history could be dated back to the late Northern dynasties and Shanxi area could be the place where it was invented. In the Tang dynasty, stone lamp platforms became flourishing in North China. As a Buddhist center in the medieval period, Mount Wutai attracted numerous pilgrims and it developed very rich and diverse Buddhist culture. Interestingly, one stone lamp platform from this area survived today. It was first commissioned in the Kaiyuan period in the early eighth century by a group of Buddhist adherents under the leadership of two Buddhist masters and renovated in the Song dynasty, in 997 by local Buddhist patrons. The inscription written by Zhang Chuzhen is mostly extant, which offers us an opportunity of understanding the historical context in which this platform was constructed. This article aims to examine the significance of this lamp platform by looking into its position with a comparison with other lamp platforms discovered in Shanxi area. It will investigate the Buddhist connections between Mount Wutai and Taiyuan, as well as the Ye City by reading a group of lamp platforms in these areas as a monastic network. In the meantime, given that the Shanxi area was a stronghold of Zoroastrians from Central Asia in the medieval period as recent archeological findings demonstrate, this article will attempt to analyze the rituals of lighting lamp platforms in Buddhism and worshipping fire temples in Zoroastrianism from cross-cultural and cross-religious perspectives.